Charge compensation phenomena for polarization discontinuities in ferroelectric superlattices - Lim, K.G.; Chew, K.H.; Wang, D.Y.; Ong, L.H.; Iwata, M. (EPL Association, European Physical Society, 2014)
Based on the Landau-Ginzburg theory, the screening charge compensation phenomena for polarization discontinuities at interface in ferroelectric superlattices are investigated. Interface mixing leads to polarization continuity or discontinuity in superlattices. Free charge with equal but of opposite sign for alternate interface, driven by internal electric field, builds up to counteract the depolarization effect in superlattices. The charge density depends on the degree of interface mixing, and it approaches a saturated value when the mismatch of internal field or polarization at interface vanishes. Using PbTiO3/SrTiO3 (PT/ST) as a model system, the charge compensation phenomena for polarization discontinuities in superlattices is investigated by examining the polarization and internal electric field profiles. Dependence of local polarization and internal field at the interfaces on screening charge density is also examined in detail. Copyright (C) EPLA, 2014